2022
DOI: 10.13057/biodiv/d230710
|View full text |Cite
|
Sign up to set email alerts
|

Application of Lactobacillus inoculant from various rice paddy (Oryza sativa) to total mixed ration silage microbial composition

Abstract: Abstract. Wahyudi A, Hendraningsih L, Sutawi S, Siskawardani DD. 2022. Application of Lactobacillus inoculant from various rice paddy (Oryza sativa) to total mixed ration silage microbial composition. Biodiversitas 23: xxxx. Evaluation of microorganisms profile of total mixed ration (TMR) silage inoculated with lactic acid bacteria (LAB) from local rice paddy (Oryza sativa L.) in tropical climate was analyzed to solve the feed management system. This study aimed to compare the effect of local LAB inoculants wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Nevertheless, it is widely acknowledged that tropical grasses inherently possess lower levels of soluble carbohydrates; Kagan et al [44] reported 6.3% WSC in Bermudagrass and 4.3% in Tifton 85 Bermudagrass before preservation [36]. Values of 1.4, 1.25, and 1.63% WSC were obtained in silage of different tropical grasses [45][46][47], similar to WSC in haylage. Understanding the dynamics of WSC content during conservation is crucial for developing strategies to enhance fermentation efficiency and improve silage nutritive value.…”
Section: Fermentative Characteristics Of African Stargrass Silage And...mentioning
confidence: 98%
“…Nevertheless, it is widely acknowledged that tropical grasses inherently possess lower levels of soluble carbohydrates; Kagan et al [44] reported 6.3% WSC in Bermudagrass and 4.3% in Tifton 85 Bermudagrass before preservation [36]. Values of 1.4, 1.25, and 1.63% WSC were obtained in silage of different tropical grasses [45][46][47], similar to WSC in haylage. Understanding the dynamics of WSC content during conservation is crucial for developing strategies to enhance fermentation efficiency and improve silage nutritive value.…”
Section: Fermentative Characteristics Of African Stargrass Silage And...mentioning
confidence: 98%